2010
DOI: 10.3109/08037051.2010.542649
|View full text |Cite
|
Sign up to set email alerts
|

An approach of hypertension prevalence in a sample of 5381 Portuguese children and adolescents. The AVELEIRA registry. “Hypertension in Children”

Abstract: The proportion of children with BP above the 90th percentile was high, with an overall prevalence of hypertension of 12.8%, independent of gender and related to overweight. The implications of these observations are even more important when we consider the epidemiology of hypertension in Portugal and its link with stroke as the leading cause of death and disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 13 publications
5
19
0
2
Order By: Relevance
“…The same was found in other studies where repeated measurements were not performed 12. We believe the true prevalence of hypertension in children as a whole (independent of body mass index (BMI)) to be somewhere in the range of 2%–4%,7 8 13 14 accounting for the fact that some children will require subsequent readings of BP to exclude false-positive results.…”
Section: Prevalence Of Hypertensionsupporting
confidence: 57%
“…The same was found in other studies where repeated measurements were not performed 12. We believe the true prevalence of hypertension in children as a whole (independent of body mass index (BMI)) to be somewhere in the range of 2%–4%,7 8 13 14 accounting for the fact that some children will require subsequent readings of BP to exclude false-positive results.…”
Section: Prevalence Of Hypertensionsupporting
confidence: 57%
“…Central-European studies showed the prevalence of HTN in adolescents to be 2.2% in Switzerland, 2.5% in Hungary and 4.9% in Poland (31)(32)(33). Data from Southern Europe identified higher prevalence; adolescent HTN was estimated as 9% in Turkey, 12% in Greece and 13% in Portugal (34)(35)(36). After the age of 10, primary HTN is the predominant form (37) and in the majority of the adolescent hypertensives, 81% were ISH (31).…”
Section: Prevalencementioning
confidence: 98%
“…The daily needs of salt intake in children are not well determined, but in a particular population of South American adults included in the Intersalt Study whose blood pressure did not rise with age, it was found to be about 0.012 g per day [18]. In Portugal, although hypertension prevalence in children has been evaluated in a few studies [19,20] there are no data on determination of salt intake in children. The aim of this work was focused on the evaluation of salt intake in a school community of 10-12 years at a school in the north of Portugal.…”
Section: Introductionmentioning
confidence: 99%